FACILITY ASSESSMENT FOR MATERNAL AND CHILD HEALTH SERVICES IN BANGLADESH USING SERVICE AVAILABILITY AND READINESS ASSESSMENT (SARA) TOOL: A CROSS-SECTIONAL PILOT STUDY - Aftab, Afzal; Hasan, Mehedi; Bari, Rahmatul; Hossain, Mohammad Didar; Hasan, Mehadi; Azad, Abul Kalam; Islam, Bulbul; Sarker, Malabika (Public Health of Indonesia, 2017)
Background: To initiate journey towards the Universal Health Coverage (UHC) it is essential to assess the health facilities. Unfortunately, no health facility assessment has been conducted in Bangladesh so far using "Service Availability and Readiness Assessment (SARA)” tool. Therefore, we aimed to conduct a pilot study to assess health facilities for maternal and child health services using SARA tool so that we can scale-up this assessment throughout the country later.Aim: We aimed to assess the health facilities for maternal and child health services in Tangail, Bangladesh using service availability and readiness assessment (SARA) tool.Methods: A cross-sectional pilot study was conducted in Bashail and Shokhipur Upazilla of Tangail district. A sample of 14 health facilities was assessed purposefully for data collection using a modified version of the SARA tool. Data was collected from November 01 to November 15, 2013, using paper-based questionnaire. Finally, following data collection, data were documented into Microsoft Excel by data collectors. Data were analyzed using Microsoft Excel, version 2010.Results: General service readiness has been segregated into five domains and their readiness scores were basic amenities (53.06%), basic equipment (83.33%), standard precautions for infection prevention (55.56%), and basic equipment (58.93%) for included health facilities. Similarly, specific service readiness includes family planning (48.15%), child immunization (67.71%), preventive and curative care (71.43%), and basic surgery (93.33%).Conclusion: Since we are moving towards UHC, it is essential to know the current scenario of health facilities. This pilot study reveals the strength and weakness of the health facilities in providing the maternal and child health services. These findings will help us to resolve all the identified gaps through proper planning and action.